PENGARUH TINGKAT PENDIDIKAN, KUALITAS PELATIHAN, DAN LAMA PENGALAMAN KERJA PEGAWAI TERHADAP KUALITAS LAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH (SKPD) DI KABUPATEN ACEH UTARA - Muzahid, Mukhlisul (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
This study aimed to test empirically the effect of educational level, quality of training,and long work experience employee either simultaneously or partially on the qualityof financial reporting unit (SKPD) in North Aceh district. The method used in thisstudy is a census method. The study was conducted in 35 work units (SKPD) in thetown of Lhokseumawe. The data used is primary data and data collection is donethrough through questionnaires. The analytical method used is descriptive analysis,and hypothesis testing methods used path analysis. The results showed thatsimultaneous levels of education, quality of training, and the long experience ofemployees affect the quality of financial reporting unit (SKPD). Partially level ofeducation, quality of training, and long work experience of each employee has apositive effect on the quality of financial reporting unit (SKPD).Keywords: educational level, quality of training, long work experience employee, andquality of financial reporting